Enantioselective Synthesis of (+)-Isolysergol via Ring Closing Metathesis - Deck, Jason A. (2010)
[Image: see text] The first enantioselective synthesis of (+)–isolysergol was completed in 12 steps from commercially available materials by a novel approach that features a late stage microwave-mediated, diastereomeric ring closing metathesis catalyzed by a chiral molybdenum catalyst to simultaneously form the D ring and set the stereocenter at C(8).